Research on the Mechanism of Power Quality in Renewable Energy Marketing Based on BMA Algorithm - Qinghua Fan (EAI Endorsed Transactions on Energy Web, 2025)
INTRODUCTION: Based on the BMA (Bayesian Model Average) algorithm, this paper deeply studies the mechanism of power quality in renewable energy marketing. By collecting a large amount of renewable energy market data and utilising the BMA algorithm for model building and data analysis, this paper aims to reveal the internal relationship between power quality and renewable energy marketing and explore its impact on actual market operations.OBJECTIVES: In the context of data analysis, this paper selects multidimensional information, including sales data, user feedback data, and power quality monitoring data, from the renewable energy market over recent years. By integrating and analysing these data with the BMA algorithm, we find that power quality has a significant positive impact on the marketing of renewable energy.METHODS: Specifically, when power quality is improved by 10%, the sales of renewable energy products are expected to increase by approximately 6% on average, and customer satisfaction will rise by 7% accordingly. This data shows that improving power quality can effectively promote the expansion of the renewable energy market and enhance user loyalty. Our research, leveraging the BMA algorithm, reveals that improving power quality serves as a dual catalyst for promoting renewable energy.RESULTS: Firstly, it directly bolsters consumer trust and purchase intention towards renewable energy products. Secondly, it indirectly enhances the market competitiveness of these products by optimising their performance and reducing failure rates. These insights provide renewable energy enterprises with a pivotal foundation for optimising their marketing strategies.CONCLUSION: In conclusion, power quality emerges as a crucial factor in the marketing of renewable energy. By prioritising its improvement, enterprises can simultaneously enhance sales, customer satisfaction, and product competitiveness, thereby underscoring the importance of power quality as a core component of their marketing strategy.
Keywords: BMA algorithm; Power Quality; Renewable energy; Marketing